P607 Clinical outcomes and immunogenicity analysis over 6 months following a switch from originator infliximab (Remicade®) to the biosimilar SB2 (Flixabi®) in inflammatory bowel disease patients. (16th January 2018) - Fischer, S; Klenske, E; Schmitt, H; Vitali, F; Hirschmann, S; Koch, F; Ramming, A; Zundler, S; Nagore, D; Uter, W; Neurath, M F; Atreya, R
Abstract: Background: The anti-tumour necrosis factor (TNF) antibody Flixabi ® is a biosimilar of the infliximab originator Remicade ® and has recently been approved in the European market for treatment of inflammatory bowel disease (IBD) patients. However, there are currently no data available regarding the clinical efficacy and the immunogenicity after switching IBD patients from Remicade ® to Flixabi ® . We therefore prospectively assessed the disease activity, safety, pharmacokinetic profile and immunogenicity over the course of 6 months following a switch from Remicade ® to Flixabi ® in IBD patients. Methods: Remicade ® treated IBD patients at the Erlangen University Hospital were switched between 02/2017 and 04/2017 to Flixabi ® and prospectively assessed for the following 6 months. Changes in the Harvey-Bradshaw Index for Crohn's disease (CD), the clinical Mayo-Score for ulcerative colitis (UC), and documented adverse events were evaluated. Infliximab through levels (TL) and anti-drug antibodies (ADA) were analysed with Promonitor ® tests. Results: In total, 119 IBD patients (53 females, 76 CD, 43 UC) were switched from Remicade ® to Flixabi ® . The mean age of the IBD patients was 41 years (19–78) and the median time of Remicade ® therapy was 132.4 weeks (2.9–478.3). Median change in disease activity was 1 (range 0.0–2.0) at Week 8, 0 (–0.8–1.8) at Week 16 and 1 (0.0–2.0) at Week 24 in CD, and 0 (−1.0–0.0) at Week 8, 0 (−1.0–0.0) at Week 16 and 0 (−1.0–0.0) at Week 24 in UC. Median through level were 6.4 μg/ml (2.5–14.5; n = 119) at Week 0 compared with 5.1 μg/ml (2.3–11.1; p = 0.15; n = 116) at Week 8, 5.6 μg/ml (2.4–10.0; p = 0.18; n = 112) at Week 16 and 4.7 μg/ml (2.7–8.3; p = 0.15; n = 101) at Week 24 for the switched IBD patients. The percentages of assessable IBD patients measured below, within and above the therapeutic TL range of 3–7 μg/ml were 28%, 26%, and 46% at Week 0 and 29%, 35%, and 36% at Week 24, respectively. Altogether, nine patients continued to have ADA, two developed new and persisting ADA, two developed new and transient ADA, and two lost ADA positivity during the follow-up of 24 weeks. Eighteen patients discontinued Flixabi ® treatment or were lost to follow-up. There was one malignancy diagnosed after the second Flixabi ® application and one ileocecal resection due to persistent disease activity after the third Flixabi ® application. No other serious adverse events occurred. Conclusions: Our data demonstrate that switching IBD patients from Remicade ® to Flixabi ® therapy in a real-life setting does not affect their clinical disease activity in the course of 6 months and is not associated with increased immunogenicity or safety signals. Consequently, these findings suggest that IBD patients can be switched from the originator Remicade ® to the biosimilar Flixabi ® .